Flat super-oscillatory lens for heat-assisted magnetic recording with sub-50nm resolution - Yuan, Guanghui (2014)
Heat-assisted magnetic recording (HAMR) is a future roadmap technology to overcome the superparamagnetic limit in high density magnetic recording. Existing HAMR schemes depend on a simultaneous magnetic stimulation and light-induced local heating of the information carrier. To achieve high-density recorded data, near-field plasmonic transducers have been proposed as light concentrators. Here we suggest and investigate in detail an alternative approach exploiting a far-field focusing device that can focus light into sub-50nm hot-spots in the magnetic recording layer using a laser source operating at 473nm. It is based on a recently introduced super-oscillatory flat lens improved with the use of solid immersion, giving an effective numerical aperture as high as 4.17. The proposed solution is robust and easy to integrate with the magnetic recording head thus offering a competitive advantage over plasmonic technology.